2020
DOI: 10.1016/j.prro.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A Blinded, Prospective Study of Error Detection During Physician Chart Rounds in Radiation Oncology

Abstract: Peer review during physician chart rounds is a major quality assurance and patient safety step in radiation oncology. However, the effectiveness of chart rounds in detecting problematic treatment plans is unknown. We performed a prospective blinded study of error detection at chart rounds to clarify the effectiveness of this quality assurance step. Methods and Materials: Radiation Oncology Incident Learning System publications were queried for problematic plans approved for treatment that would be detectable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…In a recent blinded study, Talcott et al demonstrated that traditional weekly chart rounds is only 55% effective at identifying simulated errors in presented treatment plans. 13 In response, Chera, Marks, and Potters suggest that prospective daily rounds are a potential solution, particularly in light of the technological shifts towards virtual meetings after the recent COVID-19 pandemic. 14 We found that Daily Contouring Rounds could detect errors associated with several high-risk failure modes including "FM1: Wrong or inaccurate MD contours," "FM3: Improper margins for PTV," and "FM 7: Wrong or inaccurate dosimetrist contours."…”
Section: Discussionmentioning
confidence: 99%
“…In a recent blinded study, Talcott et al demonstrated that traditional weekly chart rounds is only 55% effective at identifying simulated errors in presented treatment plans. 13 In response, Chera, Marks, and Potters suggest that prospective daily rounds are a potential solution, particularly in light of the technological shifts towards virtual meetings after the recent COVID-19 pandemic. 14 We found that Daily Contouring Rounds could detect errors associated with several high-risk failure modes including "FM1: Wrong or inaccurate MD contours," "FM3: Improper margins for PTV," and "FM 7: Wrong or inaccurate dosimetrist contours."…”
Section: Discussionmentioning
confidence: 99%
“…It is common practice for radiation oncologists to seek to minimise errors through the review of treatment plans at 'chart rounds' . In a prospective study, [11] detectable errors were inserted into treatment plans. However, these errors were detected during the review in only 55% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…A blinded prospective study of physician chart rounds reported a trend towards decreasing detection of errors with later presentation, with almost half of the problematic plans going undetected. 47 Cases should ideally be discussed prior to start of treatment as many recommendations occur earlier during the treatment workflow, 21,48,49 with major recommendations potentially being less likely to be implemented later in the workflow due to the amount of work required. 26 It may be more efficient to perform peer review in two stages, with radiotherapy planning only to commence after peer review of volumes.…”
Section: Peer Review Meeting Timing and Durationmentioning
confidence: 99%
“…However, when a larger number of cases are to be reviewed, consideration should be given to subspecialty‐specific meetings and shorter, more frequent meetings which are likely to be more effective than longer meetings. A blinded prospective study of physician chart rounds reported a trend towards decreasing detection of errors with later presentation, with almost half of the problematic plans going undetected 47 . Cases should ideally be discussed prior to start of treatment as many recommendations occur earlier during the treatment workflow, 21,48,49 with major recommendations potentially being less likely to be implemented later in the workflow due to the amount of work required 26 …”
Section: Practical Implementation Of Peer Reviewmentioning
confidence: 99%